2022
DOI: 10.1155/2022/8659462
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Modulates 5-HT4R-Mediated cAMP/PKA Signaling to Improve Intestinal Motility Disorders in a Thy1-αSyn Parkinson’s Mouse Model

Abstract: Constipation is one of the most common nonmotor symptoms in patients with Parkinson’s disease (PD) and often occurs before motor symptoms. Electroacupuncture effectively improves the symptoms of constipation in patients with PD. In the present study, we used thymus cell antigen 1-α-synuclein (Thy1-αSyn) transgenic mice as a model of intestinal motility disorders in PD to determine the therapeutic effect of electroacupuncture and the underlying mechanisms. Electroacupuncture significantly improved fecal excreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…By upregulating 5-HT and 5-HT4R in colon tissue, electroacupuncture can activate the downstream cAMP/PKA pathway, regulate the expression of related neurotransmitters SP and CGRP, and then regulate the intestinal nervous system and improve intestinal movement disorders, thereby relieving constipation in PD. [51] Evidence has found that acupuncture can treat functional constipation by promoting gastrointestinal peristalsis, regulating hormones in the peripheral gastrointestinal tract, and maintaining a balance between excitatory and inhibitory neurons in the Enteric Nervous System. [52–54]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By upregulating 5-HT and 5-HT4R in colon tissue, electroacupuncture can activate the downstream cAMP/PKA pathway, regulate the expression of related neurotransmitters SP and CGRP, and then regulate the intestinal nervous system and improve intestinal movement disorders, thereby relieving constipation in PD. [51] Evidence has found that acupuncture can treat functional constipation by promoting gastrointestinal peristalsis, regulating hormones in the peripheral gastrointestinal tract, and maintaining a balance between excitatory and inhibitory neurons in the Enteric Nervous System. [52–54]…”
Section: Discussionmentioning
confidence: 99%
“…By upregulating 5-HT and 5-HT4R in colon tissue, electroacupuncture can activate the downstream cAMP/PKA pathway, regulate the expression of related neurotransmitters SP and CGRP, and then regulate the intestinal nervous system and improve intestinal movement disorders, thereby relieving constipation in PD. [51] Evidence has found that acupuncture can treat functional constipation by promoting gastrointestinal peristalsis, regulating hormones in the peripheral gastrointestinal tract, and maintaining a balance between excitatory and inhibitory neurons in the Enteric Nervous System. [52][53][54] The results of the meta-analysis of 11 RCTs showed that acupuncture combined with conventional treatment could assist in alleviating the constipation of PD patients, effectively increase the number of spontaneous defecations, improve quality of life, increase rectal resting pressure, and lessen the severity of chronic constipation.…”
Section: Ccsmentioning
confidence: 99%